2021
DOI: 10.3389/fbioe.2021.672594
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Nanotechnology for Treatment of Alzheimer’s and Parkinson’s Disease

Abstract: The prevalence of the two most common neurodegenerative diseases, Parkinson’s disease (PD) and Alzheimer’s Disease (AD), are expected to rise alongside the progressive aging of society. Both PD and AD are classified as proteinopathies with misfolded proteins α-synuclein, amyloid-β, and tau. Emerging evidence suggests that these misfolded aggregates are prion-like proteins that induce pathological cell-to-cell spreading, which is a major driver in pathogenesis. Additional factors that can further affect patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 134 publications
0
12
0
Order By: Relevance
“…Moreover, the photothermal effect of AuNCs can also serve as an effective means to dissolve Ab amyloid deposits. Zhang et al 168 reported one type of Cys-Arg (CR) dipeptide modied Au nanocluster (Au 23 (CR) 14 ) that was able to effectively dissolve pre-formed Ab brils into monomers and recover the natural unfolded state of Ab peptides from misfolded b-sheets (Fig. 9C).…”
Section: Gold Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the photothermal effect of AuNCs can also serve as an effective means to dissolve Ab amyloid deposits. Zhang et al 168 reported one type of Cys-Arg (CR) dipeptide modied Au nanocluster (Au 23 (CR) 14 ) that was able to effectively dissolve pre-formed Ab brils into monomers and recover the natural unfolded state of Ab peptides from misfolded b-sheets (Fig. 9C).…”
Section: Gold Nanoclustersmentioning
confidence: 99%
“…[10][11][12] Among them, nanomaterials have great advantages in influencing amyloid fibril nucleation, disintegrating matured amyloid fibril, and targeting amyloid plaques via crossing the blood-brain barrier (BBB). [10,[13][14][15][16] At the same time, nanomaterials have ability to responsive to light, sound, heat, electricity, and magnetism because of the physical properties of some nanomaterials, and they have also been gradually developed and applied in the research of neurodegenerative diseases. [10,[17][18][19][20][21] Nanomaterials can be classified into one-dimensional, two-dimensional, zerodimensional, and other nanomaterials according to their dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35a,133 ] According to the previous reports, in neurodegenerative diseases, the similar pathological mechanisms of both AD and PD as described are misfolding and aggregation of proteins, and the elevated production of ROS leading to a cascade of oxidative stress and cell death. [ 134 ] Moreover, the excessive production of ROS is also a key mechanism to cause brain damage after ischemic strokes. These excessive ROS have been considered to mediate most of the damages following ischemia/reperfusion injury.…”
Section: Nanozymes Based Therapeutic Strategies For Neurodegenerative...mentioning
confidence: 99%
“…The case of lipoic acid, a chemical naturally present in the mitochondria with substantial anti-inflammatory and antioxidant capabilities capable of reducing oxidative stress, exemplifies the potential of NPS to improve the efficacy of AD therapy [87]. They are designed in such a way that they are harmless, biodegradable, and target-specific [88]. In the context of treating Alzheimer's disease, these nano systems could effectively retain and distribute medicines and other neuroprotective chemicals to the brain [89].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%